A conceptual model to measure and manage the implementation of green initiatives at South African public universities - Tshivhase, Lelo; Bisschoff, Christo (Frontiers in Sustainability, 2023)
The growing need for environmental awareness accentuated the importance of green and sustainable business practices. This is also true for universities that modernly expanded their green training and research to engage in green operational practices. This article summarises the main principles and factors of implementing green initiatives. Firstly, a generic theoretical approach conceptualizes implementing green initiatives at universities. The investigation analyses existing and current green initiatives at the universities, considers the benefits and barriers of implementing green initiatives, and develops a theoretical model for implementing green initiatives at South African public universities. This model is tested empirically with reliable data (α=.749) collected by a five-point Likert scale questionnaire administered to 144 responding green managers at eight selected South African public universities. Although the regression model explains satisfactory variance (R 2 =.862; R 2 adjusted=.841), only five of the 20 antecedents in the theoretical model are significant. They are Cost of green products (r=.527; p≤.05), Lack of awareness and training (r=.435; p≤.05), Managerial attitude and commitment (r=.369; p≤.05), Digitisation (r=.552; p≤.05), and Management Committee (r=.451; p≤.05). Further analysis revealed that the data possess embedded intelligence, and 13 factors, explaining a cumulative variance of 61.8%, were identified. Six factors are reliable and usable. The results show that an adapted conceptual model consisting of five significant literature antecedents (p≤.05) and 13 latent variables (factors) could be hypothesized. However, only six factors are reliable (α≥.57).